(3CfSGH GdCTQGa hCNHGQges - (3CHh GdMSf CMeO Hf jMji Hf LGHQ Hf OGhO, GdHdGPQj,J (B279 (3g` s ((3eMeO bfGhi eMeO s)
(3ChdgG (B:s
(3NHQ jhe GdMeQI (B: (3bGd GdhGbOi hZjQg ai QhGjJge (B: (3deG bJd YHO Gddg Hf GdRHjQ CNGg YeQh Hf GdRHjQ NWH GdfGS aPcQ jRjO Hf eYGhjI , abGd jRjO GdNehQ , hjRjO GdaLhQ , hjRjO GdaghQ s
(3BNQgG (B:s
(3bGdhG (B: (3hPcQ eQhGf WdMI aCffi Ydjg abGd (B: (3Ef CHG eMeO Cgd deG PcQJg , dcfi CYQa ef de jPcQ dNjQ bW abGd dg (B: (3OYfi CUc Yjf GHf dYjf QShd Gddg Udi Gddg Ydjg hSde GfJgi hjdjg GdLRA GdSGOS , hChdg (B: (3CeQ GdJhGHjf hNHQge HYjf GdhQOI s
(3HgG fXGe GdJYbjHIs
(3ef GdfSNI GdKGfjI faSgGs
(3bQf GdfSN (B:s
(3GdbQf GdQGHY YTQs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B1 - (3U (B267s
Keywords: (3GdJGQjNs